Comparison of Financial Performance of State-Owned Banks and National Private Banks Using Financial Ratio - Komang Yulianti; Ni Nyoman Suli Asmara Yanti (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
In Indonesia's banking sector, State-Owned Banks and National Private Banks operate under the same regulations but with different ownership structures and strategic focuses, which may lead to variations in their financial performance. This study aims to compare the financial performance of State-Owned Banks and National Private Banks listed on the Indonesia Stock Exchange for the 2020-2024 period. This study uses a quantitative approach with a comparative method through purposive sampling, where 4 state-owned banks and 5 national private banks were selected as research samples. The variables used were key financial ratios, including CAR, ROA, ROE, NIM, BOPO, and NPL. Data were analyzed using an independent t-test to identify differences in financial performance between the two groups of banks. The results showed that the financial performance of national private banks was better than that of State-Owned Banks listed on the BEI for the 2020-2024 period. There were significant differences between state-owned banks and private banks for the CAR, ROE, and NPL ratios. However, there were no significant differences in the ROA, NIM, and BOPO ratios between state-owned banks and private banks for the 2020-2024 period. These findings imply that banks in Indonesia have different management focuses based on their ownership structure. Therefore, regulators such as the Financial Services Authority (OJK) and Bank Indonesia (BI) need to strengthen credit quality monitoring policies at state-owned banks, encourage capital strengthening, and improve operational efficiency through digitalization and cost control.